New Strait Times, 25 April 2009 - Cruez, Annie Freeda (The New Straits Times Press (M) Bhd, 2009)
The Health Ministry is planning to regulate assisted reproductive technology (ART) in view of the growing number of medical facilities, both public and private , offering treatment to couple with fertility problems.